2014
DOI: 10.1039/c3nr06454a
|View full text |Cite
|
Sign up to set email alerts
|

A complex study of the fast blue luminescence of oxidized silicon nanocrystals: the role of the core

Abstract: Silicon nanocrystals (SiNCs) smaller than 5 nm are a material with strong visible photoluminescence (PL). However, the physical origin of the PL, which, in the case of oxide-passivated SiNCs, is typically composed of a slow-decaying red-orange band (S-band) and of a fast-decaying blue-green band (F-band), is still not fully understood. Here we present a physical interpretation of the F-band origin based on the results of an experimental study, in which we combine temperature (4-296 K), temporally (picosecond r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
49
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 40 publications
5
49
4
Order By: Relevance
“…We assign this spectral type to NCs with indirect-bandgap-like characteristics because (i) type-II spectra tend to be red-shifted at RT compared with type-I spectra, (ii) they exhibit blue-shift at LT, which is analogical to the one we measured for indirect-bandgap SiNCs macroscopically 33 , and (iii) at LT, their spectral fingerprint is very similar to that observed in indirect-bandgap SiNCs by other groups 25,26 . The possibility of some of the NCs emitting spectra with indirect-bandgap-like characteristics is not as odd as it might seem because (i) our SiNCs were transformed via strainengineering to a direct-bandgap material from an indirect-bandgap precursor, thus implying that some of the non-transformed NCs might have remained in the sample and single-NC spectroscopy allowed us to uncover their presence, and (ii) some of the NCs might have been unintentionally oxidized during the single-NC measurement, thus rendering them indirect.…”
Section: Type-ii Spectramentioning
confidence: 81%
See 1 more Smart Citation
“…We assign this spectral type to NCs with indirect-bandgap-like characteristics because (i) type-II spectra tend to be red-shifted at RT compared with type-I spectra, (ii) they exhibit blue-shift at LT, which is analogical to the one we measured for indirect-bandgap SiNCs macroscopically 33 , and (iii) at LT, their spectral fingerprint is very similar to that observed in indirect-bandgap SiNCs by other groups 25,26 . The possibility of some of the NCs emitting spectra with indirect-bandgap-like characteristics is not as odd as it might seem because (i) our SiNCs were transformed via strainengineering to a direct-bandgap material from an indirect-bandgap precursor, thus implying that some of the non-transformed NCs might have remained in the sample and single-NC spectroscopy allowed us to uncover their presence, and (ii) some of the NCs might have been unintentionally oxidized during the single-NC measurement, thus rendering them indirect.…”
Section: Type-ii Spectramentioning
confidence: 81%
“…This is a very fast process compared with the photoluminescence (PL) decay time in the SiNCs under study 5,24 (2 ns), which implies that the high-energy wing should not be observed. However, as a result of the strong size dependence, the relaxation time can change by several orders of magnitude with only a 10% change in size and can reach values as high as nanoseconds 32,33 . Therefore, certain NCs with suitable sizes are those in which the hothole-related high-energy wing is observed.…”
Section: Trionic Structurementioning
confidence: 99%
“…Light emission in the blue spectral range is a known phenomenon for colloidal suspensions of silicon nanoparticles (Kimura, 1999;Belomoin et al, 2000;Valenta et al, 2008) and silicon nanocrystal films (Loni et al, 1995;Canham et al, 1996;de Boer et al, 2010;Ondič et al, 2014). At the present time, there seems to be a consensus that the vast majority of reported fluorescent bands in the blue spectral range are due to localised transitions, rather than being caused by quantum confinement (Dasog et al, 2013(Dasog et al, , 2016).…”
Section: Blue Fluorescencementioning
confidence: 99%
“…Although short life-time F band emissions were believed to be originated from the core of SiNCs, 20 both F and S bands were found to be inuenced by oxygen on SiNCs. 22,23 Recently a long lived blue band and a UV band were also found to be associated with oxidized silicon.…”
mentioning
confidence: 99%
“…Besides surface states of chemical groups, other factors, such as particle sizes, also play important roles in the mechanism of the PL. 7,11,[17][18][19][20] Time resolved PL spectra revealed that there are two types of PL emissions from SiNCs, namely, fast decaying "F band" blue emissions and slow decaying "S band" red emissions. …”
mentioning
confidence: 99%